2012
DOI: 10.1016/j.immuni.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cytokine Signaling by SOCS3: Characterization of the Mode of Inhibition and the Basis of Its Specificity

Abstract: Summary Janus kinases (JAKs) are key effectors in controlling immune responses and maintaining hematopoiesis. SOCS3 (Suppressor of Cytokine Signaling-3) is a major regulator of JAK signaling and here we investigate the molecular basis of its mechanism of action. We found that SOCS3 bound and directly inhibited the catalytic domains of JAK1, JAK2 and TYK2, but not JAK3 via an evolutionarily conserved motif unique to JAKs. Mutation of this motif led to the formation of an active kinase that could not be inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
249
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(258 citation statements)
references
References 48 publications
9
249
0
Order By: Relevance
“…Facing the proline, a conserved tryptophan residue (Trp1067) is shown in yellow stick representation (see text). The side chain of the glutamine residue of the Gly-Gln-Met motif is depicted (see text) (51). Note that the activation loop, phosphorylated on Tyr…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facing the proline, a conserved tryptophan residue (Trp1067) is shown in yellow stick representation (see text). The side chain of the glutamine residue of the Gly-Gln-Met motif is depicted (see text) (51). Note that the activation loop, phosphorylated on Tyr…”
Section: Discussionmentioning
confidence: 99%
“…interaction, suppressor of cytokine signaling 3 was reported to disturb phosphate transfer to the tyrosine substrate without affecting ATP hydrolysis (51).…”
mentioning
confidence: 99%
“…In conjunction with Jian-Guo Zhang and Richard Simpson, the group showed that the SOCS box recruited elongins B and C and Cullin 5 to form an E3 ubiquitin ligase complex that ubiquitinated and targeted for proteasomal destruction any protein bound to the SH2 domain (37). In addition, two of the SOCS proteins (SOCS1 and SOCS3) contained an N-terminal sequence that could directly inhibit the catalytic activity of JAKs by binding in the substrate recognition domain of JAKs (Babon et al 2012).…”
Section: Suppressors Of Cytokine Signalling (Socs Proteins)mentioning
confidence: 99%
“…Similarly, in a prostate tumor model, targeted loss of SOCS3 in myeloid cells significantly enhanced tumor growth via regulation of myeloid-derived suppressor cells (MDSC) development and function [13]. Finally, an exciting discovery at the Walter and Eliza Hall Institute led to the identification of a novel, ATP-independent mechanism by which SOCS3 inhibits JAK catalytic activity [14]. Compared with the competitive ATP-mimetic that is currently used to inhibit JAK activity, non-competitive kinase inhibitors are highly desirable and have a selective advantage because they cannot be out-competed by endogenous ATP [15].…”
mentioning
confidence: 99%